The 256 kb mitochondrial genome of Clavaria fumosa is the largest among phylum Basidiomycota and is rich in introns and intronic ORFs - Xu Wang; Yajie Wang; Wen Yao; Jinwen Shen; Mingyue Chen; Ming Gao; Jiening Ren; Qiang Li; Na Liu (IMA Fungus)
Abstract In the present study, the complete mitogenome of Clavaria fumosa, was sequenced, assembled, and compared. The complete mitogenome of C. fumosa is 256,807 bp in length and is the largest mitogenomes among all Basidiomycota mitogenomes reported. Comparative mitogenomic analysis indicated that the C. fumosa mitogenome contained the most introns and intronic ORFs among all fungal mitogenomes. Large intergenic regions, intronic regions, accumulation of repeat sequences and plasmid-derived genes together promoted the size expansion of the C. fumosa mitogenome. In addition, the rps3 gene was found subjected to positive selection between some Agaricales species. We found frequent intron gain/loss events in Agaricales mitogenomes, and four novel intron classes were detected in the C. fumosa mitogenome. Large-scale gene rearrangements were found occurred in Agaricales species and the C. fumosa mitogenome had a unique gene arrangement which differed from other Agaricales species. Phylogenetic analysis for 76 Basidiomycetes based on combined mitochondrial gene sets indicated that mitochondrial genes could be used as effective molecular markers for reconstructing evolution of Basidiomycota. The study served as the first report on the mitogenomes of the family Clavariaceae, which will promote the understanding of the genetics, evolution and taxonomy of C. fumosa and related species.